Unsteady ultra-lean combustion of methane and biogas in a porous burner – An experimental study - Habib, Rabeeah; Yadollahi, Bijan; Saeed, Ali; Doranehgard, Mohammad Hossein; Li, Larry K.B.; Karimi, Nader (Applied thermal engineering, 2021)
•Ultra lean flames in porous media respond to oscillations in fuel flow rate.•Flame motion is almost in phase with fuel flow fluctuations.•The amplitude of motion is larger for methane flames.•Long-term exposure to fluctuations results in flame destabilisation. The response of ultra-lean flames, stabilised in a porous burner, to the fluctuations imposed on the fuel flow rate is investigated experimentally. The study is motivated by the likelihood of small biogas generators to produce fuels with temporal variations in their flow rate and chemical composition. The employed porous burner includes layers of silicon carbide porous foam placed inside a quartz tube. The burner is equipped with a series of axially arranged thermocouples and is imaged by a digital camera. Methane and a blend of methane and carbon dioxide (mimicking biogas) are mixed with air and then fed to the burner at equivalence ratios below 0.3. The fuel flow rate is modulated with a programmable mass flow controller by imposing a sinusoidal wave with variable amplitude and frequency on the steady fuel flow. Through analysis of the flame images and collected temperature traces, it is shown that the imposed disturbances result in motion of the flame inside the burner. Such motion is found to qualitatively follow the temporal variation in the fuel flow for both methane and biogas. Nonetheless, the amplitude of the flame oscillations for methane is found to be higher than that for biogas. Further, it is observed that exposure of the burner to the fuel fluctuations for a long time (180 s) eventually results in flame destabilisation. However, stabilised combustion was achieved for methane mixtures at amplitudes between 0 and 30% of steady values over a period of 60 s. This study reveals the strong effects of unsteady heat transfer in porous media upon the fluctuations in flame position.